(untitled) (Journal of actual problems of jurisprudence, 2021)
This article discusses the legal regulation of digitalization of the environment in the Republic of Kazakhstan. The author examines the current state of the environmental problem, digital environmental safety and digital ecosystems in the implementation of available technologies. Actual environmental problems, environmental crises in certain regions of our country and in the world, in general, require a logical search for solutions, including using digital ecology and the rule of law. However, there are many questions regarding the legal implementation of digitization strategies. Digital transformation affects data protection, information technology security, technical design, liability, and regulatory issues. The theoretical significance of the scientific article is explained by the fact that its results supplement the theoretical concepts of environmental law with new scientific data and results. Logical-legal, systemic, functional, comparative-legal methodology, as well as methods of legal sociology were used as research methods. The scientific novelty of this work lies in the fact that the study of the problems of digitalization of environmental information is considered as a set of legal, economic, organizational, and technical measures aimed at ensuring the environmental safety of the Republic of Kazakhstan, as well as ensuring cybersecurity in the field of environmental information. Keywords. Environmental law, environmental protection, environmental safety, environmental information, digitalization, ecosystem, platform